Density of Escherichia coli Bacteria in Blood Clams (Anadara granosa) in Anak Setatah Village, Meranti Islands Regency, Riau - Rahmanda, Melysa; Feliatra, Feliatra; Nursyirwani, Nursyirwani (Jurnal Perikanan dan Kelautan, 2025)
Blood clams are soft-bodied animals that live sessile and obtain food by filtering (filter feeders). This results in many microorganisms accumulating in the body of the blood clams, one of which is the coliform bacteria group. Coliform bacteria are divided into two types, namely fecal coliform and non-fecal coliform. Fecal coliform comes from animal and human feces, such as Escherichia coli. According to SNI 01-7388-2009, the MPN value of E. coli bacteria for fresh Mollusca, Crustaceans, and Echinodermata is <3/g. This study aimed to calculate the density of E. coli bacteria in blood clams. This study was conducted from December 2024 to February 2025. Sampling was conducted at the lowest ebb with one transect consisting of 3 plots measuring 1 × 1m². The MPN method is a method for analyzing coliform bacteria and E. coli. The results of the estimation test obtained at station 1, namely the Tebing Dian Beach Area, ranged from 7-10 MPN/g with an average of 12.6 MPN/g and station 2, namely the "Cinta Mangrove" Tourism Area, ranged from 4-15 MPN/g with an average of 10 MPN/g. While the results of the estimation test obtained at station 1 ranged from 3-4 MPN/g with an average of 2.3 MPN/g, stations 2 ranged from 3 MPN/g with an average of 1.0 MPN/g. These results indicate that the abundance of E. coli bacteria in blood clams does not exceed the quality standards set based on SNI 01-7388-2009